Differences of somatosensory evoked potential parameters at athletes - Enescu Bieru, D.; Cosma, G.; Kese, A.; Neamu, O.; Neamu, M. C. (Journal of Sport and Kinetic Movement, 2019)
The objective of our study was to measure the parameters (latencies and inter-wave latencies intervals) of somatosensory evoked potential (SEP) waves at 21 male athletes, 11 fencers and 10 handball players, active for at least 6 years in eitherone of the mentioned sports and to compare the results, in order to emphasize the influence of specific profesional training. Responses obtained by stimulating the sportsmen" median nerve, bilaterally and successively, from fist articulation, were recorded and measured using the Nihon Kohden Neuropack MEB-9100 device.From the multitude of parameters provided by the analysis ofrecorded tracks, the values of SEP? waves latencies and of inter-waves latency intervals, were statistically processed. The results has shown the existence of higher values of waves latencies, for the entire group, obtained by stimulating the right median nerve, compared to those obtained by stimulating the left hand, although subjects were right handed, due, probably to the effect of dominant member infra-clinic lesions. In comparison with the entire group, fencers had a particular aspect of left-right latency differences sense, which was inverted both for waves as for the interval that represents the specific cortex, while, handball subgroup presented significant statistical differences of the waves latenciesrepresenting the non-specific cortex.By using modern functional exploration methods, as somatosensory evoked potentials, we were able to perform an original and complex study, regarding the influence of profesional training, specific to certain categories of sports over the neurocortical activity.